Experimental Study on the Fracture Behaviors Effect of Stress Conditions on the Fracture of Shale by Super-Critical Carbon Dioxide - Liu, Guojun; Zhao, Yuan; Cheng, Yugang (Frontiers in Energy Research, 2021)
Focus on crack propagation in low permeability shale with by super-critical carbon fracturing, Acoustic emission monitoring and computerized tomography (CT) scanning methods were used in fracturing experiments, and the influence of initial stress ratios on crack initiation and propagation crack. The results show that under different stress conditions, crack initiation pressure and crack morphology are very different. Under the condition of constant confining pressure, when the initial stress ratio λ = 1, cracks are mainly in a horizontal direction; while the initial stress ratio λ < 1, cracks are mainly in a vertical direction. With the decrease of λ, crack initiation pressure, reopening pressure and fracturing liquid volume also decrease, and crack propagation is not as obvious. According to the CT scanning results, the crack propagation direction is the same as the maximum principal stress, and less cracks are initiated with a smaller initial stress ratio. Based on the acoustic emission characteristics, the fracturing process (including crack initiation, propagation and closure), can be divided into three stages: (1) the pressure accumulation in the wellbore, (2) Pump Closure; and (3) crack reopening. This study provide the basis for reasonable selection of shale gas fracturing formation and geo-sequestration of greenhouse gas CO2.